Kendali Kecepatan Dan Posisi Pada Mobile Robot Yang Menggunakan Triangle Omni-Directional Wheels Dengan Metode PID - Saputra, Aditya Wiguna; Harianto, Harianto; Mardiana, I Dewa Gede Rai (Journal of Control and Network Systems, 2014)
Mobile robot is a robot that has a drive mechanism such as wheel or foot (leg) to be able to move from one place to another place, on a mobile robot generally has a conventional design where the design has limitations that need to angle the motion area to turn around. Developments in the mobile robot control method develops very rapidly, especially in the control methods used to control the velocity of the mobile robot and the position desired by the mobile robot, one that is often used method is PID (Proportional-Integrative-Derivative) and Fuzzy.Mobile robot which uses omni-directional wheels triangle has advantage in terms of mobility within the solid to be able move all direction without having to spin in position (rafiudin, 2012), this saving travel time within a movement and is able to move in place that possesses the less. For support of the movement of a mobile robot using triangle omni-directional wheels we need a method of controlling the speed of rotation a DC motor to support the motion of a mobile robot. The method uses is PID where PID have advantages values of parameters obtained mathematically than fuzzy method where that uses try and error, the PID method we can calculate the values of the parameters used in accordance with the first method is the Ziegler Nichols oscillation.From the results of this test showed that the average error respond owned by the mobile robot is equal to 3.5885% of the X axis, the Y axis 3.8645% and 3.6205% for the orientation angle made. Where the value of the angular orientation errors obtained from mathematical calculations, the data obtained from 40 trials for each input position different purposes. In accordance with the first method of Ziegler Nichols oscillation is then obtained values for the parameters corresponding to the control of mobile robots is the value of Kp = 2.8, Ki = 5.6 and Kd = 0.84.